A Conceptual and Pedagogical Study of Object-Oriented Programming Principles Using Java (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The concept of Object-Oriented Programming is the foundation of the modern software engineering development and to implement this Java as a programming language is being widely used in the industry. Seeking its importance for real world it has been seen that beginners often struggle to understand the OOPs concept because of their early focus on syntax rather than design thinking.This article mainly focuses on the core four OOPS principles along with Class and objects. The four pillars are classified into inheritance, polymorphism, encapsulation and abstraction. The study shows how these concepts are used and finally implemented to design structured and maintainable software systems. For reusability of any feature we implement inheritance and for designing the application with the help of interface, we implement abstraction. The paper aims to bridge the gap between theoretical understanding and practical application by explaining OOP concepts using simple explanations and real-world analogies.